1995
DOI: 10.1001/archinte.1995.00430100053006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Deep-Vein Thrombosis

Abstract: Six to 8 years after deep-vein thrombosis, many patients had died of preexisting cancer or cardiovascular disease. Recurrent venous thromboembolism was uncommon. Symptoms in the leg affected by the index thrombosis were common, however, and were associated with worse health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
2
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(107 citation statements)
references
References 32 publications
4
97
2
4
Order By: Relevance
“…Research on these important patient-reported outcomes has been limited by the lack of practical, scientifically rigorous outcome measures. To date, some studies have evaluated quality of life in patients with deep venous thrombosis using generic measures alone [24,25]. Generic measures, however, do not give a full picture of the impact of deep venous thrombosis on quality of life and are less useful than disease-specific measures in evaluating change over time.…”
Section: Discussionmentioning
confidence: 99%
“…Research on these important patient-reported outcomes has been limited by the lack of practical, scientifically rigorous outcome measures. To date, some studies have evaluated quality of life in patients with deep venous thrombosis using generic measures alone [24,25]. Generic measures, however, do not give a full picture of the impact of deep venous thrombosis on quality of life and are less useful than disease-specific measures in evaluating change over time.…”
Section: Discussionmentioning
confidence: 99%
“…29 Perhaps more importantly, initial involvement of the common femoral or iliac veins is associated with a greater increase in objective (Villalta) postthrombotic scores. 8 Although the importance of recurrent venous thrombosis is well recognized as a powerful determinant of the postthrombotic syndrome, 7,31,32 involvement of the iliofemoral venous segment is associated with at least as great a mean change in Villalta score (ϩ2.23; 95% confidence interval [CI], 1.29-3.16) as a previous ipsilateral DVT (ϩ1.78; 95% CI, 0.69-2.87). 8 Finally, patients with extensive iliofemoral venous thrombosis have a greater than twofold increased risk of recurrent VTE compared with those with femoropopliteal thrombosis.…”
Section: Precision In the Diagnosis Of Dvtmentioning
confidence: 99%
“…Klinisch manifeste Lungenembolien werden in etwa 10% der Patienten beschrieben [38,39]. Aufgrund ihrer hohen Morbidität und Mortalität gilt die Lungenembolie als äußerst bedrohliches Krankheitsbild, das einer unverzüglichen Diagnostik und Therapie zugeführt werden muss.…”
Section: Thrombophiliediagnostikunclassified